Perspektif Positivisme VS Post-Positivisme dalam Memandang Ilmu Pengetahuan Bebas Nilai serta Implikasinya dalam Bimbingan dan Konseling - Abadi, Dinda Putri; Nuha, Moch. Syihabudin; Indreswari, Henny; Hotifah, Yuliati (PPPM POLTESA, 2023)
As a paradigm in science, both the Positivism paradigm and the Post-positivism paradigm have had a significant impact on the progress of knowledge and human civilization. This is also included in human development. In this process, philosophy and research methodology play an important role not only in forming science, but also in assessing the existence of science itself. The research method used in compiling this article is qualitative research through literature study. This research was carried out in several stages, namely (1) collecting data from library sources (2) processing data by citing references appropriate to the research topic (3) presenting research results (4) carrying out abstraction so that it becomes complete information (5) interpreting findings and (6) The last is drawing conclusions. The results of the study found five main characteristics of scientific knowledge, namely empirical, systematic, objective, analytical and verification. Positivism emphasizes empirical knowledge. Meanwhile, post-positivism highlights meaning, subjectivity and recognizes that knowledge is often not value-free. Guidance and counseling is a scientific practice that contains values that are reflected in the understanding of Guidance and Counseling. Guidance and counseling are closely related to values in education. Guidance and counseling are scientific practices that contain values that are reflected in the understanding of guidance and counseling. Guidance and counseling are closely related to education and bring values to education. Therefore, guidance and counseling cannot be considered value-free.